2017
DOI: 10.5897/ajmr2017.8593
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Heidelberg reduces nitrergic neurons in the myenteric plexus of the duodenum of broilers

Abstract: The present study aimed to characterize the effects of Salmonella Heidelberg challenge, as well as its changes in the inhibitory neuron subpopulation in the myenteric plexus of broilers. At the age of 21 days, after euthanasia of birds, duodenum fragments were collected from 5 male chicken broilers Cobb 500 linage from the challenged group and the control group for the quantification from the subpopulation of myenteric plexus inhibitory neurons by the histochemical method of NADPHdiaphorase. The membrane prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Studies on other bird species, such as the one by PREVIAto Do AMARAl et al (2017), found a density of 24.38±4.97 NADPH-d+/mm 2 neurons in the duodenum of broiler chickens aged 21 days. YANG et al (2013) reported 45.92±17.51 NADPH-d+/mm 2 neurons in the jejunum of broiler chickens aged 40 days.…”
Section: Resultsmentioning
confidence: 92%
“…Studies on other bird species, such as the one by PREVIAto Do AMARAl et al (2017), found a density of 24.38±4.97 NADPH-d+/mm 2 neurons in the duodenum of broiler chickens aged 21 days. YANG et al (2013) reported 45.92±17.51 NADPH-d+/mm 2 neurons in the jejunum of broiler chickens aged 40 days.…”
Section: Resultsmentioning
confidence: 92%
“…It is important to emphasize that the location of the myenteric plexus, as well as the shape and number of ganglia, studied in animals other than bats, showed that they may vary according to the species and segment of the digestive tract under study COSTA, 1980), in addition to eating habits (STABILLE et al, 2002;MUNNICH;GABEL;PFANNKUCHE, 2008;PREVIATO DO AMARAL et al, 2017). Furness and Costa (1980) emphasize that most of the nervous cell bodies of the enteric nervous system are found in the ganglia of the myenteric plexus.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the ganglionic arrangement of myenteric plexus are described in several studies (Sant' Ana et al 1997, Yang et al 2013) that mention differences in this arrangement depending on the intestinal segment and the species studied (Irwin 1931, Furness & Costa 1980, Gabella 1990, Furness 2006 as well as in different food habits (Stabille et al 2002, Münnich et al 2008, Previato do Amaral et al 2017.…”
Section: Discussionmentioning
confidence: 99%